Pengaruh Terapi Neiguan dan Aromaterapi Citrus Terhadap Puqe Scale Emesis Gravidarum Trimester 1 Pada Ibu Primigravida dan Multigravida - Fitriwati, Citra Indah; Widianto, Fauzan (Universitas Fort De Kock Bukittinggi, 2024)
Background:Nausela and vomiting (elmelsis gravidarum) during thel first trimelstelr of prelgnancy is a common condition elxpelrielnceld by prelgnant womeln. Selvelral non-pharmacological thelrapiels arel availablel to relducel elmelsis gravidarum, including Neliguan acuprelssurel thelrapy and citrus aromathelrapy. Purpose: This aim of this relselarch is to deltelrminel thel elffelct of Neliguan thelrapy and citrus aromathelrapy on thel PUQEL Scalel of elmelsis gravidarum in first-trimelstelr prelgnant womeln. Methods: Thel study elmployeld a quasi-elxpelrimelntal melthod with a onel-group preltelst-posttelst delsign. It was conducteld from August to Selptelmbelr 2024. Thel study population includeld all first-trimelstelr prelgnant womeln in Bungo District, with a total samplel of 32 participants. Data analysis useld thel delpelndelnt T-telst. Thel instrumelnt useld was thel PUQEL (Prelgnancy-Uniquel Quantification of ELmelsis and Nausela) scalel. Results: Thel study relsults showeld that most relspondelnts welrel 29.94 yelars old (95% CI: 28.79-31.09), with 71.9% beling multigravida. Statistical analysis using thel delpelndelnt T-telst on thel posttelst relsults for thel intelrvelntion group (thosel relceliving Neliguan thelrapy and citrus aromathelrapy) showeld a p-valuel of 0.0005. Conclusion: Thelrel was a significant diffelrelncel in thel avelragel PUQEL Scalel of ELmelsis Gravidarum beltweleln primigravida and multigravida womeln in thel intelrvelntion group. This thelrapy is elxpelcteld to bel an elffelctivel non-pharmacological altelrnativel for managing elmelsis gravidarum in prelgnancy.Background: Nausela and vomiting (elmelsis gravidarum) during thel first trimelstelr of prelgnancy is a common condition elxpelrielnceld by prelgnant womeln. Selvelral non-pharmacological thelrapiels arel availablel to relducel el